Implementation of the VIKOR Method and Analytical Hierarchy Process (AHP) in Prioritizing the Recipients of Uninhabitable House Assistance Funds (RTLH)” - Armonitha, Shary; Rahmansyah, Nugraha (AI Society & STMIK Indonesia, 2024)
Uninhabitable House (RTLH) is one of the social problems often faced by the community. Funding programs for RTLH repairs are important to improve the quality of life and housing conditions of the underprivileged. However, with limited resources, prioritizing the receipt of RTLH funds is a challenge. In this study, two effective multi-criteria decision-making methods, VIKOR Method and Analytical Hierarchy Process (AHP), are implemented to prioritize the receipt of RTLH funds. The combination of these two methods is expected to provide more accurate and accountable results. It is hoped that this research can provide a more holistic and objective method in prioritizing the receipt of RTLH assistance funds. The integration of the VIKOR Method and AHP can provide benefits in making similar decisions in other social and humanitarian fields, as well as helping the government and related institutions in allocating resources more efficiently and fairly. The results of this research are expected to help decision makers prioritize the receipt of RTLH funds objectively and fairly, by considering various relevant criteria.